Praktik Jual Beli di Nmtstore.id Pada Aplikasi Shopee Perspektif Hukum Islam - Saifudin Saifudin; Waluyo Sudarmaji; Muhajir Muhajir; Ikram Annafi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Looking at the current phenomenon, buying and selling using the marketplace is becoming increasingly popular, this is motivated by the ongoing corona virus pandemic, so many people choose to buy and sell using the online system. Shopee is one of the marketplaces that competes in the world of online buying and selling, by offering attractive programs, such as flash sale promos, free shopee shipping, and there is also 10,000 shopee packages. The aim of this research is to describe whether buying and selling practices on nmtstore.id on the Shopee application are in accordance with Islamic law and Islamic business ethics. The method used in this research is a qualitative method with data collection techniques through interviews, sources and literature studies used to strengthen the analysis. The results of this research explain that there is a discrepancy or the terms and conditions of sale and purchase have not been fulfilled, namely in the terms and conditions of the person entering into the contract, because the buyer and seller are the same person, in this case the contract is damaged because it does not fulfill the terms of sale and purchase and the terms of sale and purchase. carrying out the contract is a different person. Meanwhile, in the view of Islamic business ethics, purchasing one's own goods at Shopee does not violate the rules or violate the provisions of Islamic business ethics.